Exploring the genetic landscape of the Copper Homeostasis and Silver Resistance Island (CHASRI) in Salmonella enterica - Julie Haendiges; Eric W. Brown; Christina Ferreira; Maria Hoffmann; Elizabeth Reed; Jie Zheng; Rohan Tikekar (PLoS ONE, 2025)
Copper is essential for all living organisms, but becomes toxic when present in excess. Biological systems have evolved mechanisms to keep organisms in copper homeostasis. Studies have shown that Salmonella can acquire mobile genetic elements that provide enhanced tolerance to stressed environments, such as the Copper Homeostasis and Silver Resistance Island (CHASRI), which has become more prevalent in certain serovars that are exposed to higher levels of copper. In this study, whole genome sequence data available from NCBI Pathogen Detection was used to determine the incidence of the CHASRI is in Salmonella enterica isolates. The results show that the CHASRI is present in a wider range of serovars than previously known and can be found in isolates from different food sources, including nuts, spices, and produce. Salmonella Genomic Island-4 (SGI-4) was previously described as the primary mobile element through which the CHASRI was transferred to Salmonella ; however, results from this comparative study of closed reference genomes identified additional integrations of the CHASRI as both a singular mobile element and as a component of an SGI-4 variant.